2012
DOI: 10.1182/blood.v120.21.3240.3240
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Death in 632 Patients with Sickle Cell Anemia in the United States and United Kingdom

Abstract: 3240 The role of pulmonary hypertension as a common and attributable cause of mortality in patients with sickle cell disease remains controversial. To assess this question and explore risk factors for death in patients with sickle cell disease we evaluated 632 patients in the Walk-PHASST pulmonary hypertension screening cohort, recruited from nine different study sites in the United States and one site in the United Kingdom. Methods: Patient ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
4
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 0 publications
3
4
1
Order By: Relevance
“…Of the 164 patients included in our study, only 10 patients (6·1%) had a TRV value of 3·0 m/s or higher. Using the same time point as Gladwin et al () (24 months) we found similar survival estimates of 99% for TRV <3·0 m/s and 80% for TRV ≥3·0 m/s. Nonetheless, using a time point of 68 months, there was no significant difference ( P = 0·125) in the survival estimates: 95% for TRV <3·0 m/s and 80% for TRV ≥3·0 m/s.…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…Of the 164 patients included in our study, only 10 patients (6·1%) had a TRV value of 3·0 m/s or higher. Using the same time point as Gladwin et al () (24 months) we found similar survival estimates of 99% for TRV <3·0 m/s and 80% for TRV ≥3·0 m/s. Nonetheless, using a time point of 68 months, there was no significant difference ( P = 0·125) in the survival estimates: 95% for TRV <3·0 m/s and 80% for TRV ≥3·0 m/s.…”
Section: Discussionsupporting
confidence: 78%
“…Nonetheless, using a time point of 68 months, there was no significant difference ( P = 0·125) in the survival estimates: 95% for TRV <3·0 m/s and 80% for TRV ≥3·0 m/s. We also found that patients with higher TRV values had a higher risk of death (HR: 6·52; 95% CI 2·97–20·6; P = 0·001) when other factors are not considered (in comparison to a HR of 11·14 reported by Gladwin et al , ), however this risk disappears after adjustment for other variables associated with survival.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations